Pendampingan Peran Kader dalam Mengurangi Kejadian KEK Pada Ibu Hamil di PMB Sarfina Sembiring - Munthe, Juliana; Sari, Febriana; Mandala Putri, Ninsah; Nurmawan, Siti; Sari Sembiring, Isyos; Putri Utami, Lisa; Sembiring, Mediana; Sembiring, Sarfina (Al-Khidmah Jurnal Pengabdian Masyarakat, 2024)
Cadres play an important role in realizing education as providers of information regarding nutritious food, so that cadres' knowledge is very necessary in changing the nutritional awareness behavior of adolescents of reproductive age, pregnant and postpartum women, which was initially low to higher, so that in the end it will improve nutritious food consumption patterns. The aim of conducting research on cadres at clinic Sarfina Br Sembiring to determine the level of knowledge of cadres in preventing CED. The method used in providing cadre assistance counseling is the lecture method which is a way of explaining and explaining an idea, understanding or message verbally to the target group. The evaluation was carried out by measuring the level of knowledge of cadres through pretest and post test questionnaires regarding knowledge of CED prevention and the benefits of peanut honey to reduce CED and stunting. Based on the results of the outreach activities carried out, results were obtained in increasing knowledge of CED prevention among cadres at PMB Sarfina Br Sembiring. This is proven by the results of the questionnaire increasing cadres' knowledge from the pre-test results which showed that 73.33% of cadres answered questions correctly, then after counseling this increased to 90%. And the results obtained apart from increasing knowledge of cadre attitudes also increased from the pre-test results which showed that 63.33% of cadres answered questions correctly, then after counseling this increased to 80%.